PROFESI DAN PROFESIONAL DALAM BIDANG HUKUM - Ahmad Nurofik; Ilham Nasrudin; Muham Muhammad Mubarok (JOURNAL SAINS STUDENT RESEARCH, 2024)
The legal profession has a long and varied history in various societies, initially being created by religious leaders or authorities to maintain social order. Over time, the need for complex law enforcement emerged, resulting in specialized legal professionals. This development is closely related to the evolution of the legal system. Legal professionals apply, interpret, and develop the law, provide legal advice, represent clients in court, and ensure justice and the protection of individual rights. They face the challenges of technology, globalization, legal evolution, and societal demands for justice. The legal profession is governed by ethical standards and codes of conduct, and requires certain education and qualifications such as a bar exam or a practicing license. This research aims to explain the meaning of profession and professionals in the legal field In this research the author used a bibliographic method by taking references from books and journals. Where the author concludes that a profession is a field of work that requires education, special training, and often has ethical standards or codes of behavior that practitioners must follow. In a legal context, the legal profession includes various types of work related to law enforcement, such as advocate, judge, notary, legal advisor, etc. Meanwhile, professional is the subject of the word profession which shows attitudes and behavior of high expertise and competence in their field, having dedication and commitment to their work, having integrity, acting, as well as being responsible and having a high work ethic.